Institutional factors and the performance of higher education institutions in the accounting sufficiency exam - Santana, Aline Cordeiro; Souza, Bruno Barbosa de; Bazet, Marcos Paulo Tavares (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Identify the association between institutional factors and student performance in the accounting sufficiency exam. Methodology: The following institutional factors were considered: administrative category, academic organization, region and allocation of workload to the contents required in the test. The data covers the period between 2017 and 2021, including the Covid-19 pandemic period. Descriptive analysis and statistical tests were used to analyze the results. Results: There was a decrease in the median approval rate in the results from 2019 to 2021 for all Brazilian regions. Statistical tests revealed that universities in the Southeast region lead in approval rates. The lowest approval rates are concentrated in the northeast region. The course loads of Accounting Applied to the Public Sector, Accounting Theory, Accounting Auditing proved to be significant for performance in the exam. The institutional factors adopted in the present study together explain 47.40% of the variability in the exam approval rate. Other factors that may influence it include socioeconomic, contingent, and external factors. Contributions of the Study: The theoretical contribution consists in identifying the institutional factors that contribute to students' performance in the accounting sufficiency exam, so that HEIs can develop strategies and review their content to improve their approval rates, considering that the Educational Production Function Theory proposes that the academic result is the consequence of the combination of teaching, student and institutional variables. In practice, the results can be useful for coordinators of undergraduate courses in accounting sciences, who can reflect on the extent to which institutional factors are relevant to be considered in the management of courses, especially in periods of crisis.